Modified lithium-rich manganese-based positive electrode material and preparation method thereof

By covering the solid electrolyte layer and the n-type polymer polybenzodifurandione layer on the surface of the lithium-rich manganese-based positive electrode material, the problems of low Coulombic efficiency, poor cycle stability and rate performance of the material are solved, and higher electrochemical performance and better cycle stability are achieved.

CN119920882APending Publication Date: 2025-05-02HEFEI GUOXUAN HIGH TECH POWER ENERGY
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510088464.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The lithium-rich manganese-based positive electrode material has problems with low efficiency, poor cycle stability and rate performance in the first circle, which is mainly due to structural damage caused by oxygen release and unstable interface of the positive electrode/electrolyte.

Method used

By coating the solid electrolyte layer and the n-type polymer polybenzodifurandione layer on the surface of the lithium-rich manganese-based material, a modified lithium-rich manganese-based positive electrode material is formed. The solid electrolyte layer introduces oxygen vacancy in advance to stabilize the material structure, improve the diffusion rate of lithium ions and electron conductivity; the n-type polymer polybenzodifurandione layer enhances the electron conductivity, reduces contact with the electrolyte, and reduces side reactions.

Benefits of technology

It effectively improves the first Coulomb efficiency of the modified lithium-rich manganese-based cathode material, improves the rate performance and cycling performance, and improves the overall electrochemical performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119920882A_ABST
    Figure CN119920882A_ABST
Patent Text Reader

Abstract

The invention provides a modified lithium-rich manganese-based positive electrode material and a preparation method thereof. The modified lithium-rich manganese-based positive electrode material comprises a lithium-rich manganese-based material, a first coating layer and a second coating layer, the surface of the lithium-rich manganese-based material is sequentially coated with the first coating layer and the second coating layer, the first coating layer is in contact with the surface of the lithium-rich manganese-based material, the first coating layer is a solid electrolyte layer, and the second coating layer is an n-type polymer polybenzodifuran diketone layer. Oxygen vacancies are introduced into the modified lithium-rich manganese-based positive electrode material in advance, so that the surface structure of the lithium-rich manganese-based material is stabilized, and the rate capability of the modified lithium-rich manganese-based positive electrode material is improved. The surface of the lithium-rich manganese-based material coated with the solid electrolyte is further coated with a layer of conductive polymer n-type polymer polybenzodifuran diketone, so that the overall electronic conductivity of the modified lithium-rich manganese-based positive electrode material is improved, meanwhile, the contact between the modified lithium-rich manganese-based positive electrode material and an electrolyte is further reduced, the first coulombic efficiency of the modified lithium-rich manganese-based positive electrode material is improved, and the service life of the modified lithium-rich manganese-based positive electrode material is prolonged. And the rate capability and the cycle performance are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion battery positive electrode materials, and in particular to a modified lithium-rich manganese-based positive electrode material and a preparation method thereof. Background Art

[0002] With the rapid development of new energy vehicles, high energy density, long cycle life, high safety performance, and low cost have become the core issues of concern to battery and material-related companies. The energy density of lithium-ion batteries has been rising since its invention, but in recent years, the development of lithium-ion battery cathode materials has mainly focused on ternary cathode materials. With the improvement of technology, the energy density of ternary cathode materials has reached a bottleneck. Therefore, in order to meet the consumer demand of the electric vehicle market, it has become a social consensus to develop secondary batteries with higher energy density. In recent years, the demand for high energy density of power batteries has increased. Compared with traditional layered ternary cathode materials, the actual discharge capacity of lithium-rich manganese-based cathode materials has reached more than 300mAh / g, and the discharge voltage is about 3.5V. It is currently the most competitive and potential cathode material for power lithium-ion batteries. Although lithium-rich manganese-based cathode materials have the above advantages, there are also many problems: the coulomb efficiency corresponding to the first charge and discharge process is low, the interface between the electrode and the electrolyte is unstable, the lithium ion diffusion coefficient is low, the rate performance is not ideal, and the voltage decay during the cycle causes the energy density to decrease.

[0003] Among them, the problems of low first-cycle coulombic efficiency, poor cycle stability and rate performance of lithium-rich manganese-based positive electrode materials are all related to the oxygen release in the first-cycle charging process of the material, poor stability of the positive electrode / electrolyte interface and poor electronic / ionic conductivity. When charged for the first time above 4.5V, the lattice oxygen of the lithium-rich manganese-based material will precipitate, forming a large number of oxygen vacancies, causing the migration of transition metal ions and the rearrangement of the crystal structure. When the lithium ions are re-embedded, the channel is blocked, resulting in irreversible capacity loss, thus reducing the first-cycle discharge capacity and the first-cycle efficiency. At the same time, under high voltage, the lattice oxygen precipitation will be released in the form of oxygen, causing serious gas production in the battery cell. During the charge and discharge cycle of the material, the surface structure of the material deteriorates, and the side reactions at the positive electrode / electrolyte interface intensify, resulting in a gradual decrease in capacity. Lithium-rich manganese-based positive electrode materials are composed of two phases, among which the Li2MnO3 phase has electrical insulation properties, and the lithium ion diffusion channel is restricted. In particular, the side reaction products between the surface of the positive electrode material and the electrolyte seriously hinder the transmission of lithium ions and electrons at the interface, resulting in increased impedance under large currents. Summary of the invention

[0004] The main purpose of the present invention is to provide a modified lithium-rich manganese-based positive electrode material and a preparation method thereof, so as to solve the problems of low first-cycle coulombic efficiency, poor cycle stability and rate performance of lithium-rich manganese-based positive electrode materials in the prior art.

[0005] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, a modified lithium-rich manganese-based positive electrode material is provided, which comprises a lithium-rich manganese-based material and a first coating layer and a second coating layer sequentially coated on the surface of the lithium-rich manganese-based material, wherein the first coating layer is arranged in contact with the surface of the lithium-rich manganese-based material, the first coating layer is a solid electrolyte layer, and the second coating layer is an n-type polymer polybenzodifurandione layer.

[0006] The present invention coats the surface of the lithium-rich manganese-based material with a solid electrolyte layer, so that the surface structure of the lithium-rich manganese-based material is freed from Li2O to form oxygen vacancies. The oxygen vacancies are introduced in advance, which helps to alleviate the problem of structural damage caused by oxygen release during the first charge and discharge process, thereby stabilizing the surface structure of the lithium-rich manganese-based material, and then effectively improving the stability of the surface structure of the modified lithium-rich manganese-based positive electrode material. At the same time, the solid electrolyte has the characteristics of a fast ion conductor, which improves the rate performance of the modified lithium-rich manganese-based positive electrode material. A layer of conductive polymer n-type polymer polybenzodifurandione is coated on the surface of the lithium-rich manganese-based material coated with the solid electrolyte. This polymer has very excellent room temperature conductivity, thereby improving the overall electronic conductivity of the modified lithium-rich manganese-based positive electrode material, and at the same time, further reducing the contact between the modified lithium-rich manganese-based positive electrode material and the electrolyte. In addition, the charged conjugated skeleton in the n-type polymer polybenzodifurandione can generate a strong interaction with the solvent, and has excellent solution processing performance, so that the surface of the modified lithium-rich manganese-based positive electrode material and the electrolyte are well integrated together to avoid excessive side reactions. Therefore, the modified lithium-rich manganese-based positive electrode material of the present invention can effectively improve its first coulomb efficiency, improve its rate performance and cycle performance.

[0007] Furthermore, the mass ratio of the solid electrolyte layer, the n-type polymer polybenzodifurandione layer and the modified lithium-rich manganese-based positive electrode material is 0.2-2:0.01-0.1:100; and / or the ionic conductivity of the solid electrolyte layer is 1×10 -4 ~9×10 2 S / cm; and / or, the ionic conductivity of the n-type polymer polybenzofurandione layer is 100 to 2000 S / cm.

[0008] Preferably, the mass ratio of the solid electrolyte layer, the n-type polymer polybenzodifurandione layer and the modified lithium-rich manganese-based positive electrode material is controlled within the above range, which can ensure that the thickness and efficiency of each coating layer reach the optimal state, thereby further improving the charge storage capacity and cycle efficiency of the modified lithium-rich manganese-based positive electrode material. At the same time, by controlling the ionic conductivity of the solid electrolyte layer and the n-type polymer polybenzodifurandione layer within the above range, the ion transmission efficiency of the material during the charge and discharge process is ensured, the impedance is effectively reduced, and it is beneficial to improve the rate performance of the modified lithium-rich manganese-based positive electrode material.

[0009] Furthermore, the general chemical formula of the lithium-rich manganese-based material is Li 1.2 Ni 0.8x Mn 0.8y Co 0.8(1-x-y) O2, wherein 0<x<1, 0<y<1, 0<x+y≤1; and / or, the average particle size of the lithium-rich manganese-based material is 5-18μm.

[0010] Preferably controlling the chemical composition of the above lithium-rich manganese-based materials is conducive to optimizing the discharge capacity and voltage platform of the modified lithium-rich manganese-based positive electrode materials. At the same time, by controlling the average particle size of the lithium-rich manganese-based materials within the above range, it is helpful to improve the surface activity and reaction rate of the modified lithium-rich manganese-based positive electrode materials, thereby improving the overall performance of the materials.

[0011] According to another aspect of the present invention, a method for preparing the above-mentioned modified lithium-rich manganese-based positive electrode material is provided, and the preparation method comprises: step S1, calcining a raw material including a lithium-rich manganese-based material and a solid electrolyte material to obtain a modified lithium-rich manganese-based material; step S2, sequentially mixing and drying the modified lithium-rich manganese-based material and a raw material of an n-type polymer polybenzodifurandione concentrated solution to obtain a modified lithium-rich manganese-based positive electrode material; wherein the amount of lithium ions in the solid electrolyte material accounts for 0.5 to 1%.

[0012] The preparation method of the present application is to coat a solid electrolyte layer on the surface of the lithium-rich manganese-based material by calcination, so that the solid electrolyte reacts with the lithium on the surface of the lithium-rich manganese-based positive electrode material, and the solid electrolyte Li is controlled according to the lithium excess of the lithium-rich manganese-based material. + The ratio of Li in lithium-rich manganese-based materials is within the above range. + With Li in solid electrolyte +The concentration difference can control the amount of Li2O released from the surface of the lithium-rich manganese-based material. The early release of Li2O slows down the oxygen release problem during the first cycle of charging and can stabilize the surface structure of the lithium-rich material. At the same time, the solid electrolyte is coated on the surface of the lithium-rich manganese-based material to form a fast ion conductor, so that the material has a higher lithium ion diffusion rate and electronic conductivity, and the solid electrolyte has a higher diffusion rate due to smaller ion clusters, which reduces the concentration gradient during high-rate cycles. Solid electrolyte coating can improve the corrosion of the electrolyte on the surface material, reduce the side reactions at the positive electrode / electrolyte interface, and further improve the structural stability of the surface of the modified lithium-rich manganese-based positive electrode material during the cycle. In addition, coating the surface of the solid electrolyte-coated lithium-rich manganese-based material with a layer of highly conductive organic polymer is beneficial to improving the electronic conductivity of the base material, and the strong interaction between the polymer and the electrolyte is beneficial to reducing surface side reactions. The above preparation method of the present application can improve the first charge and discharge efficiency of the modified lithium-rich manganese-based positive electrode material and improve its rate performance. In addition, the preparation method of the present invention has a simple process and is easy to operate, and can comprehensively improve the electrical properties of the modified lithium-rich manganese-based positive electrode material. The method has high economic benefits and is environmentally friendly, and is suitable for industrial production.

[0013] Furthermore, the molar ratio of lithium ions in the above-mentioned solid electrolyte material to lithium ions in the lithium-rich manganese-based material is (0.6-1):1.

[0014] It is preferred to control the mass content ratio of lithium ions in the lithium-rich manganese-based material and the solid electrolyte material within the above range, which is beneficial to regulating the oxygen vacancy concentration on the surface of the modified lithium-rich manganese-based positive electrode material, further improving the first discharge efficiency and cycle stability of the modified lithium-rich manganese-based positive electrode material, and at the same time, ensuring that the ionic conductivity and electronic conductivity of the solid electrolyte layer reach the optimal state.

[0015] Furthermore, in the above step S2, the preparation process of the n-type polymer polybenzodifurandione concentrated solution includes: step S21, mixing the benzodifurandione crystals and the quinone organic matter with dimethyl sulfoxide to obtain a mixed solution; step S22, in an inert atmosphere, polymerizing the mixed solution at 60 to 100° C. to obtain a polymerization system; step S23, dialyzing, filtering and concentrating the polymerization system in sequence to obtain an n-type polymer polybenzodifurandione concentrated solution; wherein the quinone organic matter is selected from any one or more of dibromoquinone (TMQ) and idebenone The molar ratio of the benzodifurandione crystals to the quinone organic matter is 1:(1-2); and / or the mass concentration of the n-type polymer polybenzodifurandione concentrated solution is 13-17 mg / mL, and the mass ratio of the polymer polybenzodifurandione in the n-type polymer polybenzodifurandione concentrated solution to the lithium-rich manganese-based material is (0.01-0.1):100; and / or the polymerization reaction time is 20 min-60 min; and / or the viscosity of the n-type polymer polybenzodifurandione in the n-type polymer polybenzodifurandione concentrated solution is 1×10 4 ~8×10 5 mpa·s; and / or, the mass concentration of the solute in the mixed solution is 0.01 to 0.06 g / mL.

[0016] The present application limits the preparation process of the n-type polymer polybenzodifurandione concentrated solution, which is beneficial to obtaining a high-purity, high-concentration polymer solution and ensuring the uniformity and conductivity of the polymer coating layer, thereby facilitating improving the electronic conductivity of the modified lithium-rich manganese-based positive electrode material, reducing the corrosion of the electrolyte on the surface of the modified lithium-rich manganese-based positive electrode material, and further improving the rate performance and cycle stability of the modified lithium-rich manganese-based positive electrode material.

[0017] Furthermore, in the above step S1, the primary particle size of the solid electrolyte material is 20 to 300 nm; the mass of the solid electrolyte material is 0.2% to 2% of the mass of the lithium-rich manganese-based positive electrode material, and the solid electrolyte material is preferably selected from any one or more of phosphate solid electrolytes, sulfide solid electrolytes, halide solid electrolytes, oxide solid electrolytes, polymer solid electrolytes, inorganic composite solid electrolytes and organic composite solid electrolytes.

[0018] The solid electrolyte material with a primary particle size within the above range has a large specific surface area and high reaction activity, and can react well with the residual lithium on the surface of the lithium-rich manganese-based material. The smaller the primary particle size of the solid electrolyte, the better the coating uniformity, and it is easier to form uniform oxygen vacancies and coating layers on the surface of the lithium-rich manganese-based material after sintering reaction. At the same time, by controlling the amount and type of the solid electrolyte material within the above range, it is beneficial to improve the surface reaction between the solid electrolyte material and the lithium-rich manganese-based material, and a coating layer will be formed on the surface of the sample, which can effectively improve the surface ion conductivity and electronic conductivity, and then form a layer of fast ion conductor, improve the resistivity of the lithium-rich manganese-based positive electrode material powder, and improve the rate performance of the lithium-rich manganese-based positive electrode material.

[0019] Furthermore, in the above step S1, the calcination atmosphere is air or oxygen, and / or the calcination temperature is 350-650° C., and / or the calcination time is 3-8 hours.

[0020] The calcination conditions are preferably controlled within the above range, which is beneficial to improving the uniform coating and performance optimization of the solid electrolyte layer, ensuring the integrity of the surface structure of the modified lithium-rich manganese-based positive electrode material and the smoothness of the lithium ion diffusion path, thereby improving the electrochemical performance and service life of the modified lithium-rich manganese-based positive electrode material.

[0021] Furthermore, the preparation method also includes a preparation process of a lithium-rich manganese-based material, the preparation process comprising: mixing and sintering a lithium-rich manganese-based precursor and a raw material of a lithium salt in sequence to obtain a lithium-rich manganese-based material; wherein the lithium-rich manganese-based precursor is Ni m Mn n Co (1-m-n) (OH)2 and / or Ni m Mn n Co (1-m-n) CO3, and 0<m<1, 0<n<1, 0<m+n≤1; and / or, the lithium salt is Li2CO3; and / or, the sintering temperature is 850℃~950℃, and the sintering time is 10~15h.

[0022] The present application limits the preparation process of the lithium-rich manganese-based material and controls the chemical composition and sintering conditions of the lithium-rich manganese-based precursor within the above-mentioned range, which is conducive to the preparation of a lithium-rich manganese-based positive electrode material with high capacity, high stability and good rate performance, thereby providing a high-quality base material for subsequent surface modification.

[0023] According to another aspect of the present invention, a lithium-ion battery is provided, comprising a positive electrode sheet and a negative electrode sheet, wherein the positive electrode sheet comprises a positive electrode material, and the positive electrode material is the above-mentioned modified lithium-rich manganese-based positive electrode material.

[0024] The lithium-ion battery of the present invention, because it adopts the modified lithium-rich manganese-based positive electrode material of the present invention, is conducive to improving the initial coulombic efficiency, discharge capacity, rate performance and cycle stability of the lithium-ion battery, and can comprehensively improve the electrochemical performance of the battery.

[0025] The technical solution of the present invention is applied. The present invention coats the surface of the lithium-rich manganese-based material with a solid electrolyte layer, so that the surface structure of the lithium-rich manganese-based material is freed from Li2O to form oxygen vacancies. The oxygen vacancies are introduced in advance, which helps to alleviate the problem of structural damage caused by oxygen release during the first charge and discharge process, thereby stabilizing the surface structure of the lithium-rich manganese-based material, and then effectively improving the stability of the surface structure of the modified lithium-rich manganese-based positive electrode material. At the same time, the solid electrolyte has the characteristics of a fast ion conductor, which improves the rate performance of the modified lithium-rich manganese-based positive electrode material. A layer of conductive polymer n-type polymer polybenzodifurandione is coated on the surface of the lithium-rich manganese-based material coated with the solid electrolyte. This polymer has very excellent room temperature conductivity, thereby improving the overall electronic conductivity of the modified lithium-rich manganese-based positive electrode material, and at the same time, further reducing the contact between the modified lithium-rich manganese-based positive electrode material and the electrolyte. In addition, the charged conjugated skeleton in the n-type polymer polybenzodifurandione can generate a strong interaction with the solvent, and has excellent solution processing performance, so that the surface of the modified lithium-rich manganese-based positive electrode material and the electrolyte are well integrated together to avoid excessive side reactions. Therefore, the modified lithium-rich manganese-based positive electrode material of the present invention can effectively improve its first coulomb efficiency, improve its rate performance and cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0027] Figure 1 The XRD patterns of Example 1 and Comparative Example 1 according to the present invention are shown;

[0028] Figure 2 SEM images of Example 1 and Comparative Example 1 according to the present invention are shown;

[0029] Figure 3 The charge and discharge curves of button-type batteries according to Example 1 of the present invention and Comparative Example 1 are shown. DETAILED DESCRIPTION

[0030] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0031] As analyzed in the background technology of this application, the lithium-rich manganese-based positive electrode materials in the prior art have the problems of low first-cycle coulombic efficiency, poor cycle stability and rate performance. In order to solve this problem, this application provides a modified lithium-rich manganese-based positive electrode material and a preparation method.

[0032] In a typical embodiment of the present application, a modified lithium-rich manganese-based positive electrode material is provided, which includes a lithium-rich manganese-based material and a first coating layer and a second coating layer sequentially coated on the surface of the lithium-rich manganese-based material, the first coating layer is arranged in contact with the surface of the lithium-rich manganese-based material, the first coating layer is a solid electrolyte layer, and the second coating layer is an n-type polymer polybenzodifurandione layer.

[0033] The present invention coats the surface of the lithium-rich manganese-based material with a solid electrolyte layer, so that the surface structure of the lithium-rich manganese-based material is freed from Li2O to form oxygen vacancies. The oxygen vacancies are introduced in advance, which helps to alleviate the problem of structural damage caused by oxygen release during the first charge and discharge process, thereby stabilizing the surface structure of the lithium-rich manganese-based material, and then effectively improving the stability of the surface structure of the modified lithium-rich manganese-based positive electrode material. At the same time, the solid electrolyte has the characteristics of a fast ion conductor, which improves the rate performance of the modified lithium-rich manganese-based positive electrode material. A layer of conductive polymer n-type polymer polybenzodifurandione is coated on the surface of the lithium-rich manganese-based material coated with the solid electrolyte. This polymer has very excellent room temperature conductivity, thereby improving the overall electronic conductivity of the modified lithium-rich manganese-based positive electrode material, and at the same time, further reducing the contact between the modified lithium-rich manganese-based positive electrode material and the electrolyte. In addition, the charged conjugated skeleton in the n-type polymer polybenzodifurandione can generate a strong interaction with the solvent, and has excellent solution processing performance, so that the surface of the modified lithium-rich manganese-based positive electrode material and the electrolyte are well integrated together to avoid excessive side reactions. Therefore, the modified lithium-rich manganese-based positive electrode material of the present invention can effectively improve its first coulomb efficiency, improve its rate performance and cycle performance.

[0034] In one embodiment of the present application, the mass ratio of the solid electrolyte layer, the n-type polymer polybenzodifurandione layer and the modified lithium-rich manganese-based positive electrode material is 0.2-2:0.01-0.1:100; and / or the ionic conductivity of the solid electrolyte layer is 1×10 -4 ~9×10 2 S / cm; and / or, the ionic conductivity of the n-type polymer polybenzofurandione layer is 100 to 2000 S / cm.

[0035] Preferably, the mass ratio of the solid electrolyte layer, the n-type polymer polybenzodifurandione layer and the modified lithium-rich manganese-based positive electrode material is controlled within the above range, which can ensure that the thickness and efficiency of each coating layer reach the optimal state, thereby further improving the charge storage capacity and cycle efficiency of the modified lithium-rich manganese-based positive electrode material. At the same time, by controlling the ionic conductivity of the solid electrolyte layer and the n-type polymer polybenzodifurandione layer within the above range, the ion transmission efficiency of the material during the charge and discharge process is ensured, the impedance is effectively reduced, and it is beneficial to improve the rate performance of the modified lithium-rich manganese-based positive electrode material.

[0036] In one embodiment of the present application, the general chemical formula of the lithium-rich manganese-based material is Li 1.2 Ni 0.8x Mn 0.8y Co 0.8(1-x-y) O2, wherein 0<x<1, 0<y<1, 0<x+y≤1; and / or, the average particle size of the lithium-rich manganese-based material is 5-18μm.

[0037] Preferably controlling the chemical composition of the above lithium-rich manganese-based materials is conducive to optimizing the discharge capacity and voltage platform of the modified lithium-rich manganese-based positive electrode materials. At the same time, by controlling the average particle size of the lithium-rich manganese-based materials within the above range, it is helpful to improve the surface activity and reaction rate of the modified lithium-rich manganese-based positive electrode materials, thereby improving the overall performance of the materials.

[0038] In another typical embodiment of the present application, a method for preparing a modified lithium-rich manganese-based positive electrode material is provided, the preparation method comprising: step S1, calcining a raw material including a lithium-rich manganese-based material and a solid electrolyte material to obtain a modified lithium-rich manganese-based material; step S2, sequentially mixing and drying the modified lithium-rich manganese-based material and a raw material of an n-type polymer polybenzodifurandione concentrated solution to obtain a modified lithium-rich manganese-based positive electrode material; wherein the amount of lithium ions in the solid electrolyte material accounts for 0.5 to 1%.

[0039] The preparation method of the present application is to coat a solid electrolyte layer on the surface of the lithium-rich manganese-based material by calcination, so that the solid electrolyte reacts with the lithium on the surface of the lithium-rich manganese-based positive electrode material, and the solid electrolyte Li is controlled according to the lithium excess of the lithium-rich manganese-based material. + The ratio of Li in lithium-rich manganese-based materials is within the above range. + With Li in solid electrolyte +The concentration difference can control the amount of Li2O released from the surface of the lithium-rich manganese-based material. The early release of Li2O slows down the oxygen release problem during the first cycle of charging and can stabilize the surface structure of the lithium-rich material. At the same time, the solid electrolyte is coated on the surface of the lithium-rich manganese-based material to form a fast ion conductor, so that the material has a higher lithium ion diffusion rate and electronic conductivity, and the solid electrolyte has a higher diffusion rate due to smaller ion clusters, which reduces the concentration gradient during high-rate cycles. Solid electrolyte coating can improve the corrosion of the electrolyte on the surface material, reduce the side reactions at the positive electrode / electrolyte interface, and further improve the structural stability of the surface of the modified lithium-rich manganese-based positive electrode material during the cycle. In addition, coating the surface of the solid electrolyte-coated lithium-rich manganese-based material with a layer of highly conductive organic polymer is beneficial to improving the electronic conductivity of the base material, and the strong interaction between the polymer and the electrolyte is beneficial to reducing surface side reactions. The above preparation method of the present application can improve the first charge and discharge efficiency of the modified lithium-rich manganese-based positive electrode material and improve its rate performance. In addition, the preparation method of the present invention has a simple process and is easy to operate, and can comprehensively improve the electrical properties of the modified lithium-rich manganese-based positive electrode material. The method has high economic benefits and is environmentally friendly, and is suitable for industrial production.

[0040] In one embodiment of the present application, the molar ratio of lithium ions in the solid electrolyte material to lithium ions in the lithium-rich manganese-based material is (0.6-1):1.

[0041] It is preferred to control the mass content ratio of lithium ions in the lithium-rich manganese-based material and the solid electrolyte material within the above range, which is beneficial to regulating the oxygen vacancy concentration on the surface of the modified lithium-rich manganese-based positive electrode material, further improving the first discharge efficiency and cycle stability of the modified lithium-rich manganese-based positive electrode material, and at the same time, ensuring that the ionic conductivity and electronic conductivity of the solid electrolyte layer reach the optimal state.

[0042] In one embodiment of the present application, in the above step S2, the preparation process of the n-type polymer polybenzodifurandione concentrated solution includes: step S21, mixing the benzodifurandione crystals and the quinone organic matter with dimethyl sulfoxide to obtain a mixed solution; step S22, in an inert atmosphere, polymerizing the mixed solution at 60 to 100° C. to obtain a polymerization system; step S23, dialyzing, filtering and concentrating the polymerization system in sequence to obtain an n-type polymer polybenzodifurandione concentrated solution; wherein the quinone organic matter is selected from any of dibromoquinone (TMQ) and idebenone One or more, the molar ratio of benzodifurandione crystals to quinone organic matter is 1:(1-2); and / or, the mass concentration of the n-type polymer polybenzodifurandione concentrated solution is 13-17 mg / mL, and the mass ratio of the polymer polybenzodifurandione in the n-type polymer polybenzodifurandione concentrated solution to the lithium-rich manganese-based material is (0.01-0.1):100; and / or, the polymerization reaction time is 20 min-60 min; and / or, the viscosity of the n-type polymer polybenzodifurandione in the n-type polymer polybenzodifurandione concentrated solution is 1×10 4 ~8×10 5 mpa·s; and / or, the mass concentration of the solute in the mixed solution is 0.01 to 0.06 g / mL.

[0043] The present application limits the preparation process of the n-type polymer polybenzodifurandione concentrated solution, which is beneficial to obtaining a high-purity, high-concentration polymer solution and ensuring the uniformity and conductivity of the polymer coating layer, thereby facilitating improving the electronic conductivity of the modified lithium-rich manganese-based positive electrode material, reducing the corrosion of the electrolyte on the surface of the modified lithium-rich manganese-based positive electrode material, and further improving the rate performance and cycle stability of the modified lithium-rich manganese-based positive electrode material.

[0044] In one embodiment of the present application, in the above step S1, the primary particle size of the solid electrolyte material is required to be 20 to 300 nm; the mass of the solid electrolyte material is 0.2% to 2% of the mass of the lithium-manganese-rich positive electrode material, and the solid electrolyte material is preferably selected from any one or more of phosphate solid electrolytes, sulfide solid electrolytes, halide solid electrolytes, oxide solid electrolytes, polymer solid electrolytes, inorganic composite solid electrolytes and organic composite solid electrolytes.

[0045] The solid electrolyte material with a primary particle size within the above range has a large specific surface area and high reaction activity, and can react well with the residual lithium on the surface of the lithium-rich manganese-based material. The smaller the primary particle size of the solid electrolyte, the better the coating uniformity, and it is easier to form uniform oxygen vacancies and coating layers on the surface of the lithium-rich manganese-based material after sintering reaction. At the same time, by controlling the amount and type of the solid electrolyte material within the above range, it is beneficial to improve the surface reaction between the solid electrolyte material and the lithium-rich manganese-based material, and a coating layer will be formed on the surface of the sample, which can effectively improve the surface ion conductivity and electronic conductivity, and then form a layer of fast ion conductor, improve the resistivity of the lithium-rich manganese-based positive electrode material powder, and improve the rate performance of the lithium-rich manganese-based positive electrode material.

[0046] In one embodiment of the present application, in the above step S1, the calcination atmosphere is air or oxygen, and / or the calcination temperature is 350-650° C., and / or the calcination time is 3-8 hours.

[0047] The calcination conditions are preferably controlled within the above range, which is beneficial to improving the uniform coating and performance optimization of the solid electrolyte layer, ensuring the integrity of the surface structure of the modified lithium-rich manganese-based positive electrode material and the smoothness of the lithium ion diffusion path, thereby improving the electrochemical performance and service life of the modified lithium-rich manganese-based positive electrode material.

[0048] In one embodiment of the present application, the above-mentioned preparation method also includes a preparation process of a lithium-rich manganese-based material, the preparation process comprising: mixing and sintering a lithium-rich manganese-based precursor and a raw material of a lithium salt in sequence to obtain a lithium-rich manganese-based material; wherein the lithium-rich manganese-based precursor is Ni m Mn n Co (1-m-n) (OH)2 and / or Ni m Mn n Co (1-m-n) CO3, and 0<m<1, 0<n<1, 0<m+n≤1; and / or, the lithium salt is Li2CO3; and / or, the sintering temperature is 850℃~950℃, and the sintering time is 10~15h.

[0049] The present application limits the preparation process of the lithium-rich manganese-based material and controls the chemical composition and sintering conditions of the lithium-rich manganese-based precursor within the above-mentioned range, which is conducive to the preparation of a lithium-rich manganese-based positive electrode material with high capacity, high stability and good rate performance, thereby providing a high-quality base material for subsequent surface modification.

[0050] The above mixing is preferably carried out using a high-speed mixing device, which is preferably selected from any one of a three-dimensional motion mixer, a conical mixer, a dry powder high mixer and a plowshare mixer, and the mixing time is preferably 20 to 60 minutes.

[0051] In another typical embodiment of the present application, a lithium-ion battery is provided, including a positive electrode sheet and a negative electrode sheet, wherein the positive electrode sheet includes a positive electrode material, and the positive electrode material is the above-mentioned modified lithium-rich manganese-based positive electrode material.

[0052] The lithium-ion battery of the present invention, because it adopts the modified lithium-rich manganese-based positive electrode material of the present invention, is conducive to improving the initial coulombic efficiency, discharge capacity, rate performance and cycle stability of the lithium-ion battery, and can comprehensively improve the electrochemical performance of the battery.

[0053] The beneficial effects of the present application will be further illustrated below in conjunction with embodiments.

[0054] Example 1

[0055] A method for preparing a lithium-rich manganese-based material comprises the following steps:

[0056] Weigh 1000g Ni 0.35 Mn 0.65 (OH)2, weigh 616g lithium carbonate (Li2CO3) and mix it in a dry high-speed mixer for 30min. Put the mixed materials in a sagger, put them in a box-type atmosphere furnace, and sinter them in an air atmosphere at 910℃ for 15h to prepare lithium-rich manganese-based material Li 1.2 Ni 0.28 Mn 0.52 O2.

[0057] Weigh 300g of the above-mentioned lithium-rich manganese-based positive electrode material Li 1.2 Ni 0.28 Mn 0.52 O2, weigh 3.0g LATP (Li 1.3 Al 0.3 Ti 1.7 (PO4)3, primary particle size of 20-150nm), mixed by a dry high-speed mixer for 30min, the evenly mixed material was placed in a sagger, put into a box-type atmosphere furnace, and sintered for 5h at 500℃ in an air atmosphere to obtain a lithium-rich manganese-based material coated with a solid electrolyte.

[0058] 400 mg of benzofurandione crystals and 600 mg of dibromoquinone were dissolved in 30 mL of dimethyl sulfoxide solvent, and the reaction mixture was evacuated at room temperature and filled with nitrogen. Then, the reaction mixture was heated to 100°C with vigorous stirring, and the solution gradually changed from light yellow to dark brown. After 1 hour of reaction, a significant increase in viscosity could be observed. The reaction mixture was cooled to room temperature, and 50 mL of dimethyl sulfoxide solvent was injected to dilute the mixture. The solvent was injected into a dialysis bag, which was pretreated with an aqueous sodium bicarbonate solution and deionized water. The dialysis bag was immersed in pure dimethyl sulfoxide solvent for dialysis. The dimethyl sulfoxide solvent was replaced every 3 days. The whole process took about 2 weeks until the dimethyl sulfoxide solvent outside the dialysis bag became colorless. The polymer solution in the dialysis bag was then collected and filtered with a 0.45 μm polytetrafluoroethylene filter. The filter needed to be replaced every 30 mL. 2 mL of the filtered solution was taken and the dimethyl sulfoxide solvent was removed under high vacuum by a rotary evaporator connected to an oil pump. The resulting polymer fiber was thoroughly washed with dichloromethane, vacuum dried and weighed to obtain the concentration of the n-type polymer polybenzodifurandione concentrate at this time. The remaining n-type polymer polybenzodifurandione concentrate was fixed to a concentration of about 15 mg / mL. Weigh 30 g of solid electrolyte-coated lithium-rich manganese-based material and add it to 30 mL of n-type polymer polybenzodifurandione concentrate (viscosity 8×10 5 mpa·s), stirred for 5 min, filtered and dried to obtain the modified lithium-rich manganese-based positive electrode material.

[0059] Example 2

[0060] The difference from Example 1 is that 300 g of lithium-rich manganese-based material Li 1.2 Ni 0.28 Mn 0.52 O2, weigh 4.5g LATP (Li 1.1 Al 0.1 Ti 1.9 (PO4)3, primary particle size is 20-150nm), and finally a modified lithium-rich manganese-based positive electrode material is obtained.

[0061] Example 3

[0062] The difference from Example 1 is that 1000 g Ni 0.25 Mn 0.75 (OH)2, weigh 612g lithium carbonate (Li2CO3) and mix it in a dry high-speed mixer for 50min. Put the mixed materials in a sagger, put them in a box-type atmosphere furnace, and sinter them in an air atmosphere at 920℃ for 15h to prepare lithium-rich manganese-based material Li 1.2 Ni 0.2 Mn 0.6 O2, and finally obtain a modified lithium-rich manganese-based positive electrode material.

[0063] Example 4

[0064] The difference from Example 1 is that 1000 g Ni 0.1625 Mn 0.675 Co 0.1625 (OH)2, weigh 610g lithium carbonate (Li2CO3) and mix it in a dry high-speed mixer for 50min, put the mixed materials in a sagger, put them in a box-type atmosphere furnace, and sinter them in an air atmosphere at 900℃ for 15h to prepare lithium-rich manganese-based material Li 1.2 Ni 0.13 Mn 0.54 Co 0.13 O2, and finally obtain a modified lithium-rich manganese-based positive electrode material.

[0065] Example 5

[0066] The difference from Example 1 is that the mass of the solid electrolyte material is 0.2% of the mass of the lithium-rich manganese-based positive electrode material, and a modified lithium-rich manganese-based positive electrode material is finally obtained.

[0067] Example 6

[0068] The difference from Example 1 is that the mass of the solid electrolyte material is 2% of the mass of the lithium-rich manganese-based positive electrode material, and finally a modified lithium-rich manganese-based positive electrode material is obtained.

[0069] Example 7

[0070] The difference from Example 1 is that the mass of the solid electrolyte material is 0.1% of the mass of the lithium-rich manganese-based positive electrode material, and a modified lithium-rich manganese-based positive electrode material is finally obtained.

[0071] Example 8

[0072] The difference from Example 1 is that the n-type polymer polybenzodifurandione and the lithium-rich manganese-based material Li 1.2 Ni 0.28 Mn 0.52 The mass ratio of O2 is 0.01:100, and a modified lithium-rich manganese-based positive electrode material is finally obtained.

[0073] Example 9

[0074] The difference from Example 1 is that the n-type polymer polybenzodifurandione and the lithium-rich manganese-based material Li 1.2 Ni 0.28 Mn 0.52 The mass ratio of O2 is 0.1:100, and a modified lithium-rich manganese-based positive electrode material is finally obtained.

[0075] Example 10

[0076] The difference from Example 1 is that the n-type polymer polybenzodifurandione and the lithium-rich manganese-based material Li 1.2 Ni 0.28 Mn 0.52 The mass ratio of O2 is 0.005:100, and a modified lithium-rich manganese-based positive electrode material is finally obtained.

[0077] Embodiment 11

[0078] The difference from Example 1 is that the viscosity of the n-type polymer polybenzodifurandione is 5×10 4 mpa·s, and finally a modified lithium-rich manganese-based positive electrode material was obtained.

[0079] Example 12

[0080] The difference from Example 1 is that the viscosity of the n-type polymer polybenzodifurandione is 6×10 5 mpa·s, and finally a modified lithium-rich manganese-based positive electrode material was obtained.

[0081] Embodiment 13

[0082] The difference from Example 1 is that the viscosity of the n-type polymer polybenzodifurandione is 2×10 3 mpa·s, and finally a modified lithium-rich manganese-based positive electrode material was obtained.

[0083] Comparative Example 1

[0084] Weigh 1000g N i0.35 Mn 0.65 (OH)2, weigh 616g lithium carbonate (Li2CO3) and mix it in a dry high-speed mixer for 30min. Put the mixed materials in a sagger, put them in a box-type atmosphere furnace, and sinter them in an air atmosphere at 910℃ for 15h to prepare lithium-rich manganese-based material Li 1.2 Ni 0.28 Mn 0.52 O2 as a modified lithium-rich manganese-based positive electrode material.

[0085] Comparative Example 2

[0086] The difference from Example 1 is that the solid electrolyte material is LATP (Li 1.3 Al 0.3 Ti 1.7 (PO4)3, in which the amount of lithium ions accounts for 0.4%, and finally a modified lithium-rich manganese-based positive electrode material is obtained.

[0087] Comparative Example 3

[0088] The difference from Example 1 is that the solid electrolyte material is LATP (Li 1.3 Al 0.3 Ti1.7 (PO4)3, in which the amount of lithium ions accounts for 0.45%, and finally a modified lithium-rich manganese-based positive electrode material is obtained.

[0089] Comparative Example 4

[0090] The difference from Example 1 is that the lithium-rich manganese-based material coated with the solid electrolyte of Example 1 is directly used as the modified lithium-rich manganese-based positive electrode material.

[0091] The XRD spectra, SEM images and button cell charge and discharge curves of Example 1 and Comparative Example 1 are shown in the following order: Figure 1 , Figure 2 and Figure 3 shown.

[0092] The finished products prepared in the above embodiments and comparative examples are used as positive electrode materials, lithium sheets are used as negative electrodes, superconducting carbon black Super P is used as a conductive agent, polyvinylidene fluoride (PVDF) is used as a binder, and N-methylpyrrolidone (NMP) is used as a solvent. The positive electrode material and superconducting carbon black Super P are ground and then added to a solution of N-methylpyrrolidone dissolved with polyvinylidene fluoride. The mass ratio of the positive electrode material, Super P and PVDF is 8:1:1. After stirring for 2 hours, the mixture is coated on the surface of a 20μm thick aluminum foil and then vacuum dried at 110°C for 20 hours. The dried pole piece is rolled, sliced, and weighed, and then assembled into a CR2016 button battery with a metal lithium sheet and a diaphragm prepared by a wet process in an argon atmosphere glove box. The electrolyte is 1.0mol / LLiPF6 / EC+DEC+EMC.

[0093] The assembled button cells were subjected to electrochemical performance tests. The charge and discharge voltage range in the first week was 2.0-4.8V, and the charge and discharge tests were carried out at a rate of 0.1C. After the second week, the voltage range was 2.0-4.5V, and the charge and discharge tests were carried out at 0.1C, 0.33C, and 1C, respectively. Detailed data are shown in Table 1.

[0094] Table 1

[0095]

[0096]

[0097] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:

[0098] The present invention coats the surface of the lithium-rich manganese-based material with a solid electrolyte layer, so that the surface structure of the lithium-rich manganese-based material is freed from Li2O to form oxygen vacancies. The oxygen vacancies are introduced in advance, which helps to alleviate the problem of structural damage caused by oxygen release during the first charge and discharge process, thereby stabilizing the surface structure of the lithium-rich manganese-based material, and then effectively improving the stability of the surface structure of the modified lithium-rich manganese-based positive electrode material. At the same time, the solid electrolyte has the characteristics of a fast ion conductor, which improves the rate performance of the modified lithium-rich manganese-based positive electrode material. A layer of conductive polymer n-type polymer polybenzodifurandione is coated on the surface of the lithium-rich manganese-based material coated with the solid electrolyte. This polymer has very excellent room temperature conductivity, thereby improving the overall electronic conductivity of the modified lithium-rich manganese-based positive electrode material, and at the same time, further reducing the contact between the modified lithium-rich manganese-based positive electrode material and the electrolyte. In addition, the charged conjugated skeleton in the n-type polymer polybenzodifurandione can generate a strong interaction with the solvent, and has excellent solution processing performance, so that the surface of the modified lithium-rich manganese-based positive electrode material and the electrolyte are well integrated together to avoid excessive side reactions. Therefore, the modified lithium-rich manganese-based positive electrode material of the present invention can effectively improve its first coulomb efficiency, improve its rate performance and cycle performance.

[0099] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A modified lithium-rich manganese-based positive electrode material, characterized in that: The modified lithium-rich manganese-based positive electrode material includes a lithium-rich manganese-based material and a first coating layer and a second coating layer sequentially coated on the surface of the lithium-rich manganese-based material, wherein the first coating layer is arranged in contact with the surface of the lithium-rich manganese-based material, the first coating layer is a solid electrolyte layer, and the second coating layer is an n-type polymer polybenzodifurandione layer.

2. The modified lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The mass ratio of the solid electrolyte layer, the n-type polymer polybenzodifurandione layer and the modified lithium-rich manganese-based positive electrode material is 0.2-2:0.01-0.1:100; and / or the ionic conductivity of the solid electrolyte layer is 1×10 -4 ~9×10 2 S / cm; and / or, the ionic conductivity of the n-type polymer polybenzofurandione layer is 100-2000 S / cm.

3. The modified lithium-rich manganese-based positive electrode material according to claim 1 or 2, characterized in that: The general chemical formula of the lithium-rich manganese-based material is Li 1.2 Ni 0.8x Mn 0.8y Co 0.8(1-x-y) O2, wherein 0<x<1, 0<y<1, 0<x+y≤1; and / or, the average particle size of the lithium-rich manganese-based material is 5-18μm.

4. A method for preparing the modified lithium-rich manganese-based positive electrode material according to any one of claims 1 to 3, characterized in that: The preparation method comprises: Step S1, calcining raw materials including a lithium-rich manganese-based material and a solid electrolyte material to obtain a modified lithium-rich manganese-based material; Step S2, sequentially mixing and drying the modified lithium-rich manganese-based material and the raw material of the concentrated solution of the n-type polymer polybenzodifurandione to obtain a modified lithium-rich manganese-based positive electrode material; The amount of lithium ions in the solid electrolyte material is 0.5-1%.

5. The preparation method according to claim 4, characterized in that: The molar ratio of lithium ions in the solid electrolyte material to lithium ions in the lithium-rich manganese-based material is (0.6-1):

1.

6. The preparation method according to claim 4 or 5, characterized in that: In the step S2, the preparation process of the n-type polymer polybenzodifurandione concentrated solution comprises: Step S21, mixing the benzofurandione crystals and the quinone organic matter with dimethyl sulfoxide to obtain a mixed solution; Step S22, in an inert atmosphere, subjecting the mixed solution to a polymerization reaction at 60-100° C. to obtain a polymerization system; Step S23, dialyzing, filtering and concentrating the polymerization system in sequence to obtain the n-type polymer polybenzodifurandione concentrated solution; Wherein, the quinone organic matter is selected from any one or more of dibromoquinone (TMQ) and idebenone, and the molar ratio of the benzodifurandione crystal to the quinone organic matter is 1:(1-2); and / or, the mass concentration of the n-type polymer polybenzodifurandione concentrated solution is 13-17 mg / mL, and the mass ratio of the polymer polybenzodifurandione in the n-type polymer polybenzodifurandione concentrated solution to the lithium-rich manganese-based material is (0.01-0.1):100; And / or, the polymerization reaction time is 20min to 60min; And / or, the viscosity of the n-type polymer polybenzodifurandione in the n-type polymer polybenzodifurandione concentrated solution is 1×10 4 ~8×10 5 mpa·s; And / or, the mass concentration of the solute in the mixed solution is 0.01 to 0.06 g / mL.

7. The preparation method according to any one of claims 4 to 6, characterized in that: In the step S1, the primary particle size of the solid electrolyte material is 20 to 300 nm; the mass of the solid electrolyte material is 0.2% to 2% of the mass of the lithium-rich manganese-based positive electrode material, and the solid electrolyte material is preferably selected from any one or more of phosphate solid electrolytes, sulfide solid electrolytes, halide solid electrolytes, oxide solid electrolytes, polymer solid electrolytes, inorganic composite solid electrolytes and organic composite solid electrolytes.

8. The preparation method according to any one of claims 4 to 7, characterized in that In the step S1, the calcination atmosphere is air or oxygen, and / or the calcination temperature is 350-650° C., and / or the calcination time is 3-8 hours.

9. The preparation method according to any one of claims 4 to 8, characterized in that: The preparation method also includes a preparation process of the lithium-rich manganese-based material, and the preparation process includes: The lithium-rich manganese-based precursor and the raw materials of the lithium salt are sequentially mixed and sintered to obtain the lithium-rich manganese-based material; Wherein, the lithium-rich manganese-based precursor is Ni m Mn n Co (1-m-n) (OH)2 and / or Ni m Mn n Co (1-m-n) CO3, and 0< m<1, 0<n<1, 0<m+n≤1; And / or, the lithium salt is Li2CO3; And / or, the sintering temperature is 850° C. to 950° C., and the sintering time is 10 to 15 hours.

10. A lithium ion battery, characterized in that: It comprises a positive electrode sheet and a negative electrode sheet, wherein the positive electrode sheet comprises a positive electrode material, and is characterized in that the positive electrode material is a modified lithium-rich manganese-based positive electrode material according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Double-coated lithium-rich manganese-based material as well as preparation method and application thereof

    CN112421000A

  • High-performance all-solid-state lithium ion battery with stable structure and preparation method thereof

    CN114865100A

  • In-situ coated high-voltage positive electrode material as well as preparation method and application thereof

    CN115863651A

  • Electrode material containing n-type conductive polymer and preparation and application thereof

    CN117239049A

  • Modified phosphate positive electrode material as well as preparation method and application thereof

    CN117673349A